2017
DOI: 10.20448/journal.508.2017.41.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of Steel Slag Used in Stabilizing Expansive Soil

Abstract: This paper presents an experimental study in stabilization of expansive soil using Steel Slag (SS). Experimental program was conducted to evaluate the influence of Steel Slag on improving the engineering properties of expansive clay. A series of tests to measure consistency limits, free swell index, compaction parameters and unconfined compressive strength of natural and stabilized soils. The effectiveness of adding 0, 5, 10, 15, 20, and 30 percentages of SS to the soil was studied. Comparing the results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Alternatively, using quicklime due to its elevated reaction temperature enables stabilization in cold regions. [22,123]. Figure 7 indicates the global annual cement production between 1925 and 2009 and the cement production in various countries with China taking the lead as it plans to construct 40 billion square meters of floor space until 2036.…”
Section: Stabilizermentioning
confidence: 99%
“…Alternatively, using quicklime due to its elevated reaction temperature enables stabilization in cold regions. [22,123]. Figure 7 indicates the global annual cement production between 1925 and 2009 and the cement production in various countries with China taking the lead as it plans to construct 40 billion square meters of floor space until 2036.…”
Section: Stabilizermentioning
confidence: 99%
“…Similar to the performance of lime in stabilizing dispersive soils [ 29 , 30 , 31 ], the cation exchange, flocculation and agglomeration, and pozzolanic reaction can occur as a clayey soil reacts with certain free oxides in SFS. Various research studies have been conducted to employ SFS to enhance the properties of problematic soils, while primarily demonstrating that SFS can be an effective stabilization agent [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. From the early 1990s, Akinmusuru [ 43 ] pioneered the attempt to use SFS in soil stabilization for rural roads with low traffic volume, which suggests that SFS possesses the potential to improve the soil properties by increasing the strength, California bearing ratio (CBR), and dry density.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of Akinwumi [ 42 ] concluded that the addition of SFS to lateritic soil increased the dry density, decreased the optimum moisture content, and, as the percent SFS increased, the soaked and un-soaked CBR and the unconfined compressive strength increased. Zumrawi and Babikir [ 47 ] studied the effectiveness of adding 5%, 10%, 15%, 20%, and 30% of SFS to an expansive soil and reported that the addition of SFS improved soil properties. Abdi [ 49 ] investigated stabilizing a kaolinite soil with a combination of BOF slag and hydrated lime, which demonstrated that higher BOF slag with lime contents yielded higher compressive strengths.…”
Section: Introductionmentioning
confidence: 99%
“…[20] stated that the addition of eggshell powder to the expansive soil increased from 5 % to 20 %. After adding eggshell powder, linear shrinkage decreased by 10 % after 28 days, the maximum dry density of the expansive soil decreased from 1.323 g/cm 3 to 1.293 g/cm 3 . In addition, there was an increase in geotechnical characteristics after adding 5 % eggshell powder, compressive strength at collapse and strain increased by 18 % and 9 %, compared to expansive soil without treatment.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the combination of lime (5 %) and eggshell powder (5 %) can induce about 15 % buildup in compressive strength. While the CBR value of the soil increased from 2 % [3] conducted an experimental study of expansive soil stabilization using steel slag (SS). Experiments were conducted to evaluate the effect of steel slag on improving the engineering properties of expansive clay.…”
Section: Introductionmentioning
confidence: 99%